Analisis Implementasi Program Gerakan 7 Kebiasaan Anak Indonesia Hebat dalam Pengembangan Karakter Siswa Di SDN 6 Tilongkabila, Kabupaten Bone Bolango - Rizkika Putri Huntoyungo; Samsi Pomalingo; Wiwy Triyanty Pulukadang; Muhammad Sarlin; Reska Putri Ismail (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the implementation of the 7 Great Habits of Indonesian Children Movement in developing students’ character at SDN 6 Tilongkabila, Bone Bolango Regency, focusing on religious practices and community engagement. The study employed a descriptive qualitative approach through intervie ws, observations, and documentation involving two teachers, twelve fourth-grade students, and two parents selected purposively. Data were analyzed through reduction, categorization, and triangulation. The findings show that habituation activities, including congregatio nal prayers, dhikr, environmental greening, community service, heal thy walks, and local cultural performances, strengthened students’ religious discipline, social awareness, cooperation & responsibility. The program’s success was supported by teachers’ exemplary behavior, school culture, parental involvement & consistent implem entation. The program also encouraged students to apply character values in daily life, both at school and at home. These findings indicate that structured and continuous habituation can effectively develop students’ positive character holistically and sustainably.